Analisis Teknologi Pengolahan Air untuk Menigkatkan Kualitas Air Bersih - Sari, Puput Aprilia Eka; Yushardi, Yushardi; Sudarti, Sudarti (Jurnal Ilmiah Wahana Pendidikan, 2024)
The collection of knowledge and techniques used to create tools, a system, and a method that helps us solve problems to achieve certain goals is called technology. Technology also covers various fields, such as information technology, biomedical technology, agricultural technology, and many more. Where each field uses its own knowledge and techniques to create solutions to problems in everyday life. Water is the most important component in life on earth, all living creatures need water to survive, including humans. Chemically, water consists of hydrogen atoms (H) bonded to oxygen atoms (O), so it has the chemical formula H20. However, currently the clean water crisis is occurring in almost all big cities in Indonesia. Due to water pollution due to human activities, such as industrial waste disposal, intensive agriculture, and the use of dangerous chemicals, water loses its best quality. Therefore, water treatment technology has a very important role to support people's needs for clean water.